A phase 2a, randomized, double-blind, placebo-controlled trial of the efficacy and safety of the oral gonadotropin-releasing hormone antagonist, ASP1707, in postmenopausal female patients with rheumatoid arthritis taking methotrexate. Issue 1 (2nd January 2021) - Takeuchi, Tsutomu; Tanaka, Yoshiya; Higashitani, Chieri; Iwai, Megumi; Komatsu, Kanji; Akazawa, Rio; Lademacher, Christopher
Abstract: Objectives: Many patients with rheumatoid arthritis (RA) are not able to achieve long-term disease remission. This phase 2a study (NCT02884635) evaluated the efficacy, safety, pharmacokinetics, and pharmacodynamics of the novel, oral, gonadotropin-releasing hormone antagonist, ASP1707, in combination with methotrexate (MTX) for treatment of RA. Methods: Postmenopausal women with RA who had been receiving MTX for ≥90 days were randomized to ASP1707 30 mg twice daily or placebo for 12 weeks. The primary endpoint was the American College of Rheumatology 20% improvement criteria (ACR20) response rate at week 12. Secondary endpoints included: ACR20, ACR50, and ACR70 response rates; disease activity score (DAS)28-CRP; DAS28-ESR; Tender or Swollen Joint Counts; and remission rates. Results: Of 105 patients screened, 72 were randomized to ASP1707 30 mg twice daily ( n  = 37) or placebo ( n  = 35). ASP1707 did not improve ACR20, ACR50, or ACR70 response rates at any time point and did not improve any secondary efficacy endpoint. Plasma luteinizing hormone (LH) concentration decreased >90% in >90% of patients receiving ASP1707, with a rapid decrease to <1 IU/L at week 1 that remained stable throughout the treatment. Conclusion: In the current study, ASP1707 did not demonstrate a clinical benefit.